2021
DOI: 10.2196/preprints.28371
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sentiment Analysis of Users’ Reviews on COVID-19 Contact Tracing Apps with a Benchmark Dataset (Preprint)

Abstract: BACKGROUND Contact tracing has been globally adopted in the fight to control the infection rate of COVID-19. Thanks to digital technologies, such as smartphones and wearable devices, contacts of COVID-19 patients can be easily traced and informed about their potential exposure to the virus. To this aim, several interesting mobile applications have been developed. However, there are ever-growing concerns over the working mechanism and performance of these applications. The literature alr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
(30 reference statements)
0
5
0
2
Order By: Relevance
“…Moreover, previous research analyzing media content concerning the implementation of CTAs has identified thresholds and challenges experienced by users and showed the need to intensify communication about the benefits of using the apps [ 48 ]. By scraping social media and analyzing app users’ reviews, comments, and reported technical issues, developers could collect input to address reported issues and further develop CTA functionalities [ 4 , 49 ]. Also, by conducting in-depth interviews with potential users and analyzing media coverage on CTAs, the framing of the app’s functionalities and discussed issues can be detected [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous research analyzing media content concerning the implementation of CTAs has identified thresholds and challenges experienced by users and showed the need to intensify communication about the benefits of using the apps [ 48 ]. By scraping social media and analyzing app users’ reviews, comments, and reported technical issues, developers could collect input to address reported issues and further develop CTA functionalities [ 4 , 49 ]. Also, by conducting in-depth interviews with potential users and analyzing media coverage on CTAs, the framing of the app’s functionalities and discussed issues can be detected [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…We made the data set publicly available for researchers to further explore the potential of NLP techniques for the automatic analysis of user feedback on contact tracing applications [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Contact tracing yang diterapkan pada awalnya bersifat manual tracing dimana ketika orang yang terinfeksi virus memberikan informasi dengan siapa dan dimana ia melakukan kontak fisik dengan orang lain. Namun, penerapan manual tracing ini membuang banyak waktu dan sumber daya [2]. Dalam perkembangan teknologi pada saat ini, teknologi seperti smartphone dapat dimanfaatkan untuk membantu pemerintah melakukan tracing.…”
Section: Pendahuluanunclassified